2006
DOI: 10.1080/09603100500511068
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic news effects on conditional volatilities in the bond and stock markets

Abstract: This paper investigates the sources of time-varying risk for the US stock and bond markets. The model captures the change in the risk premium due to each market's own volatility risk and the covariance risk. We test for the effects of macroeconomic news on time-varying volatility as well as time-varying covariance, and whether such news induces time-varying risk premia in either of the markets. We find that stocks and bonds have higher volatility on the day of macroeconomic announcements. This higher volatilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…While existing literature acknowledges the importance of the levels of macroeconomic factors in determining CDS spreads, we show that the second moments of these factors-macroeconomic uncertainty-have significant explanatory power over and above that of traditional macroeconomic factors such as the risk-free rate and the Treasury term spread. Our results nicely complement the empirical findings re-ported by Arnold and Vrugt (2008) and Arshanapalli, d'Ouville, Fabozzi and Switzer (2006).…”
Section: Introductionsupporting
confidence: 80%
“…While existing literature acknowledges the importance of the levels of macroeconomic factors in determining CDS spreads, we show that the second moments of these factors-macroeconomic uncertainty-have significant explanatory power over and above that of traditional macroeconomic factors such as the risk-free rate and the Treasury term spread. Our results nicely complement the empirical findings re-ported by Arnold and Vrugt (2008) and Arshanapalli, d'Ouville, Fabozzi and Switzer (2006).…”
Section: Introductionsupporting
confidence: 80%
“…Arshanapalli et al (2006) found stock and bond prices to be more volatile on days of macroeconomic announcements. Nofsinger and Prucyk (2003) found support for the impact of macroeconomic news on the volume and volatility of the Standard & Poor's (S&P) 100 stock index options, with most of the high volume and volatility coming from announcements considered bad news.…”
Section: Existing Evidence On the Role Of Newsmentioning
confidence: 97%
“…Analysis of this reduced rank property gives an indication of co-jumping on any day, despite the current lack of a formal test directly analagous to the univariate test given in equation (8).…”
Section: Multivariate Extensionmentioning
confidence: 99%
“…An area of considerable interest in the recent theoretical high frequency literature has been the development of a multivariate counterpart to the univariate jump test given in equation (8). This jump test would be used to identify when simultaneous discontinuities are observed in the price series for two or more assets.…”
Section: Cojumpingmentioning
confidence: 99%